Psychosocial stressors among Ghanaians in rural and urban Ghana and Ghanaian migrants in Europe. (March 2022) - Awuah, Raphael Baffour; de-Graft Aikins, Ama; Dodoo, F Nii-Amoo; Meeks, Karlijn AC; Beune, Eric JAJ; Klipstein-Grobusch, Kerstin; Addo, Juliet; Smeeth, Liam; Bahendeka, Silver K; Agyemang, Charles
Psychosocial stressors have significant health and socio-economic impacts on individuals. We examined the prevalence and correlates of psychosocial stressors among non-migrant and migrant Ghanaians as there is limited research in these populations. The study was cross-sectional and quantitative in design. A majority of the study participants had experienced stress, discrimination and negative life events. Increased age, female sex, strong social support and high sense of mastery were associated with lower odds of experiencing psychosocial stressors in both populations. Interventions should be multi-level in design, focusing on the correlates which significantly influence the experience of psychosocial stressors